The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18502/ijph.v48i4.1004
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Variables in Children and Adolescents regarding the Age and Sex

Abstract: Background: This study aimed to assess the basic red blood cell variables and hematological indices in children and adolescents and analyze the differences regarding age and sex. Methods: Overall, 320 young participants, age 8 to 18 yr, were enrolled at Laboratory of Sport’s Medicine, Medical Faculty, Skopje, Macedonia in 2016. Capillary blood samples were drawn and following hematologic parameters were measured: the red blood cell count (RBC), hemoglobin concentration (Hb), hematocrit level (Hct) and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…On the other hand, a study performed in Tanzanian children aged 13-18 years showed higher RBC count, haemoglobin and haematocrit, but lower MCV in boys when compared to girls ( 20 ). However, our study participants were younger than those included in the above-mentioned studies, suggesting that differences in haematological markers in children should be further considered with respect to gender and age, but also ethnicity ( 19 , 20 ). The latest report from the CALIPER study enrolling 536 children and adolescents of multi-ethnic origin aged 0-21 years has shown that neither haematocrit, MCV or RDW values differed between sexes in the age group correspondent to our study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…On the other hand, a study performed in Tanzanian children aged 13-18 years showed higher RBC count, haemoglobin and haematocrit, but lower MCV in boys when compared to girls ( 20 ). However, our study participants were younger than those included in the above-mentioned studies, suggesting that differences in haematological markers in children should be further considered with respect to gender and age, but also ethnicity ( 19 , 20 ). The latest report from the CALIPER study enrolling 536 children and adolescents of multi-ethnic origin aged 0-21 years has shown that neither haematocrit, MCV or RDW values differed between sexes in the age group correspondent to our study.…”
Section: Discussionmentioning
confidence: 84%
“…Gender differences in haemoglobin level ad RBC indices are well known in adult populations, but these variations are not sufficiently explored in children ( 18 ). Recently, a study of age and sex differences in RBC variables was conducted in a population of Macedonian children aged 8-18 years ( 19 ). The authors reported higher values of RBC variables in boys, which is in contrast to our results.…”
Section: Discussionmentioning
confidence: 99%
“…The normal iron markers in children with SCA may be attributed to increased red cell turnover and repeated blood transfusion. The values in under-five and male subjects were lowest in this study, probably due to age variability factor and low socioeconomic status [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 90%
“…Iheanacho et al [ 8 ] and Rao et al [ 18 ] have reported higher Hb in males, although they were not statistically significant. The younger age of male subjects and the predominantly low socioeconomic status of under-five subjects in the current study might explain the observed low mean Hb [ 17 , 19 ]. The mean MCV, MCH and MCHC, which are the markers of iron status, were all within normal ranges [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study was done at the Institute of Medical and Applied Physiology and Anthropology, Faculty of Medicine, UKIM, in Skopje, the Republic of North Macedonia, between September 2016 and March 2017. Some findings concerning the investigated population in this paper have been published before (Pluncević Gligoroska et al, 2019).…”
Section: Methodsmentioning
confidence: 94%